2015
DOI: 10.3389/fpls.2015.00395
|View full text |Cite
|
Sign up to set email alerts
|

Fructans and other water soluble carbohydrates in vegetative organs and fruits of different Musa spp. accessions

Abstract: The water soluble carbohydrates (WSC) glucose, fructose, and sucrose are well-known to the great public, but fructans represent another type of WSC that deserves more attention given their prebiotic and immunomodulatory properties in the food context. Although the occurrence of inulin-type fructo-oligosaccharides (FOS) was proposed in the fruit of some banana accessions, little or no information is available neither on the exact identity of the fructan species, nor on the fructan content in different parts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Until the current data, the following oligosaccharides were identified in the banana pulp: 1‐kestose (1‐kestotriose, GF 2 ), 1,1‐nystose (GF 3 ), 1 F ‐β‐fructofuranosyl‐nystose (GF 4 ) (Campbell et al, ; Der Agopian et al, ), 6‐kestotriose, 6 G ‐kestotriose (older name, neokestose), bifurcose (1,6‐kestotetraose), inulobiose (F 2 ), and inulotriose (F 3 ) (Cruz‐Cárdenas et al, ; Der Agopian et al, ). In our study, the chromatographic analysis showed the presence of 1‐kestose, xylopentaose and xylohexaose, whereas the last two compounds were identified for the first time in the banana pulp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Until the current data, the following oligosaccharides were identified in the banana pulp: 1‐kestose (1‐kestotriose, GF 2 ), 1,1‐nystose (GF 3 ), 1 F ‐β‐fructofuranosyl‐nystose (GF 4 ) (Campbell et al, ; Der Agopian et al, ), 6‐kestotriose, 6 G ‐kestotriose (older name, neokestose), bifurcose (1,6‐kestotetraose), inulobiose (F 2 ), and inulotriose (F 3 ) (Cruz‐Cárdenas et al, ; Der Agopian et al, ). In our study, the chromatographic analysis showed the presence of 1‐kestose, xylopentaose and xylohexaose, whereas the last two compounds were identified for the first time in the banana pulp.…”
Section: Resultsmentioning
confidence: 99%
“…Banana is a good source of minerals, carbohydrates and fiber such as pectin and resistant starch (Der Agopian, Purgatto, Cordenunsi, & Lajolo, ; Englyst & Cummings, ; Mitsou et al, ). Recent studies also showed that banana has remarkable amounts of oligosaccharides, especially fructans type FOS (fructooligosaccharides) and short‐chain inulins, such as 1‐kestose (1‐kestotriose, GF 2 ), 1,1‐nystose (Der Agopian, Soares, Purgatto, Cordenunsi, & Lajolo, ), 6‐kestotriose, 6G‐kestotriose (older name, neokestose), bifurcose (1,6‐kestotetraose), inulobiose (F 2 ), and inulotriose (F 3 ) (Cruz‐Cárdenas et al, ; Der Agopian, Purgatto, Cordenunsi, & Lajolo, ). In addition, the banana shows low glycemic index (Hettiaratchi, Ekanayake, & Welihinda, ), positive effect on the fecal microbiota of healthy adult women when consumed daily (Mitsou et al, ) and contribute to maintain a good performance when consumed before or during physical exercise (Nieman et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Method Summary: The extracellular medium was analyzed to identify the chemical nature of the transformation of cellobiose carbon source as a function of growth time using HPLC and 1 H‐NMR spectroscopy (Fig. ).…”
Section: Resultsmentioning
confidence: 99%